Hubungan Pola Asuh Autoritarian Terhadap Perilaku Makan Anak - Sekar Nirmala, Eleonora (Jurnal Syntax Fusion, 2023)
Eating behavior in children and all of its problems can be influenced by many factors, one of which is parenting. Of all the parenting styles that have developed in general, the authoritarian parenting style that still dominates parents in Asia, including Indonesia, is capable of causing eating behavior problems in children. This study aims to determine the relationship between authoritarian parenting adopted by parents on eating behavior in early childhood. The participants of this study were 124 parents with children aged 0-5 years. The research method used is quantitative research with a survey using the PSDQ and CEBQ instruments. Data will be analyzed through descriptive test and Pearson correlation test with the help of the Jamovi 2.2.5 program for Windows. The results of this study indicate that authoritarian parenting style has a significant positive relationship with responsiveness to food, emotional overeating , responsiveness to satiety, emotional undereating, and picky eating (p<0.005).